Suspended InAs nanowire Josephson junctions assembled via dielectrophoresis. (25th September 2015) - Montemurro, D; Stornaiuolo, D; Massarotti, D; Ercolani, D; Sorba, L; Beltram, F; Tafuri, F; Roddaro, S
Abstract We present a novel technique for the realization of suspended Josephson junctions based on InAs semiconductor nanowires. The devices are assembled using a technique of drop-casting guided by dielectrophoresis, which allows one to finely align the nanostructures on top of the electrodes. The proposed architecture removes the interaction between the nanowire and the substrate which is known to influence disorder and the orientation of the Rashba vector. The relevance of this approach in view of the implementation of hybrid Josephson junctions based on semiconducting nanowires coupled with high-temperature superconductors is discussed.